2006
DOI: 10.1021/jp063565b
|View full text |Cite
|
Sign up to set email alerts
|

Large-Area Highly-Oriented SiC Nanowire Arrays:  Synthesis, Raman, and Photoluminescence Properties

Abstract: Large-area highly oriented SiC nanowire arrays have been fabricated by chemical vapor reaction using an ordered nanoporous anodic aluminum oxide (AAO) template and a graphite reaction cell. Their microstructures were characterized by scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction and high-resolution transmission electron microscopy. The results show that the nanowires are single-crystalline beta-SiC's with diameters of about 30-60 nm and lengths of about 8 microm, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 47 publications
9
71
3
Order By: Relevance
“…21) As shown in the Raman spectra of the as-received products (Fig. 5), however, no obvious LO phonon peak can be observed, which is similar to the results reported by Fréchette et al 22) and Li et al 23) The products obtained at 1500°C for different time have an intensive TO phonon peak with a same peak position at 785 cm…”
Section: ¹1supporting
confidence: 88%
“…21) As shown in the Raman spectra of the as-received products (Fig. 5), however, no obvious LO phonon peak can be observed, which is similar to the results reported by Fréchette et al 22) and Li et al 23) The products obtained at 1500°C for different time have an intensive TO phonon peak with a same peak position at 785 cm…”
Section: ¹1supporting
confidence: 88%
“…In the case of SiC NWs, many different Raman studies have been reported [32,46,49,53,54]. A typical example is shown in figure 11 (after [46]).…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…A UV emission around 380 nm has been also observed [54,58]. Zhang et al [58] performed a detailed study combining PL, Raman and TEM methods to identify the origin of the UV emission at 378 nm and they attributed it to threefold stacking faults, which structurally resemble to 6H-SiC layers of 1.5 nm thickness embedded in a 3C-SiC matrix.…”
Section: Photoluminescencementioning
confidence: 99%
“…Silicon carbide embodies some very useful properties like low mass density, high-thermal conductivity (350-490 W m À1 K À1 ) [1], strong resistance towards oxidation, and high mechanical strength and hardness, which makes it a potential material for many industrial applications [2][3][4]. Crystalline or amorphous silicon carbide is a semiconductor material, which has some unique electrical and electronic qualities [1,5] facilitating applications at high temperatures, high frequencies, high fields, and high powers [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Crystalline or amorphous silicon carbide is a semiconductor material, which has some unique electrical and electronic qualities [1,5] facilitating applications at high temperatures, high frequencies, high fields, and high powers [6,7]. Materials with such properties and which, additionally, can be easily formed with meso-or nanoporosity, should also be strongly solicited for applications in catalysis, gas reforming reactions, sensors, biotechnology, fuel cells, for hydrogen storage, and as hydrogen sources [8].…”
Section: Introductionmentioning
confidence: 99%